Individual-level income and out-of-hospital cardiac arrest survival in men and women. Issue 2 (19th August 2022) - van Dongen, Laura Helena; Smits, Robin L A; van Valkengoed, Irene G M; Elders, Petra; Tan, Hanno; Blom, Marieke T
Abstract : Objective: Area-level socioeconomic factors are known to associate with chances to survive out-of-hospital cardiac arrest (OHCA survival). However, the relationship between individual-level socioeconomic factors and OHCA survival in men and women is less established. This study investigated the association between individual-level income and OHCA survival in men and women, as well as its contribution to outcome variability and mediation by resuscitation characteristics. Methods: A cross-sectional cohort study using data from a Dutch community-based OHCA registry was performed. We included 5395 patients aged≥25 years with OHCA from a presumed cardiac cause. Household income, derived from Statistics Netherlands, was stratified into quartiles. The association between survival to hospital discharge and household income was analysed using multivariable logistic regression adjusting for age, sex and resuscitation characteristics. Results: Overall women had lower household income than men (median €18 567 vs €21 015), and less favourable resuscitation characteristics. Increasing household income was associated with increased OHCA survival in both men and women in a linear manner (Q4 vs Q1: OR 1.63 95% CI (1.24 to 2.16) in men, and 2.54 (1.43 to 4.48) in women). Only initial rhythm significantly changed the ORs for OHCA survival with>10% in both men and women. Household income explained 3.8% in men and 4.3% in women of the observed variance in OHCA survival. Conclusion: Both in men and women, higher individual-level household income was associated with a 1.2-fold to 2.5-fold increased OHCA survival to hospital discharge, but explained only little of outcome variability. A shockable initial rhythm was the most important resuscitation parameter mediating this association. Our results do not support the need for immediate targeted interventions on actionable prehospital resuscitation care characteristics.